HUBUNGAN PEMBERIAN NUTRISI TERHADAP PERTUMBUHAN BAYI DENGAN RIWAYAT BERAT BADAN LAHIR RENDAH (BBLR) - Diyanatul Mustafidah; Noor Azizah; Ummi Kulsum (Nusantara Hasana Journal, 2026)
Infants with a history of Low Birth Weight (LBW) are at a higher risk of experiencing growth disturbances in early life. Appropriate nutritional provision—whether through exclusive breastfeeding, formula feeding, or a combination of both—plays a crucial role in supporting the growth of LBW infants. However, in practice, variations in feeding patterns persist and may influence infant growth outcomes, particularly during the age of 1–6 months. This study aimed to determine the association between nutritional provision and growth among infants with a history of Low Birth Weight (LBW) in the working area of Puskesmas Kaliwungu. A retrospective study design was employed. The study population consisted of all infants aged 1–6 months with a history of LBW within the working area of Puskesmas Kaliwungu. A total of 38 infants were included as the sample, selected using a total sampling technique. Data were collected through observation sheets and records from the Maternal and Child Health Handbook (Kartu Menuju Sehat/KMS). Data analysis was conducted using univariate and bivariate methods, with the Fisher’s Exact test applied for statistical analysis. The univariate analysis indicated that the majority of infants with a history of LBW received combined nutrition (breast milk and formula), accounting for 63.2%. Most infants were also classified as having normal growth based on the weight-for-age (WFA) indicator (76.3%). The bivariate analysis using Fisher’s Exact test demonstrated no significant association between nutritional provision and growth among infants with a history of LBW (p-value = 1.000; p > 0.05). In conclusion, this study found no significant relationship between nutritional provision and growth among infants with a history of Low Birth Weight (LBW) in the working area of Puskesmas Kaliwungu.